Peningkatan Fungsi Manajer Keperawatan dalam Optimalisasi Komunikasi Efektif saat Handover - Ermi Rabiuliya; Hanny Handiyani; Dewi Gayatri; Astuti Giantini; Bejo Utomo; Muhammad Hadi (Journal of Telenursing (JOTING), 2023)
This research aims to describe the planned change process using Kurt Lewin's theory to optimize effective communication during ward handovers by improving the nursing manager's function. The method used is a case study including assessment activities, problem analysis, preparation of planning of action (POA), implementation, and evaluation. The research results show that in the unfreezing phase, problems were found that the performance of effective communication during the handover was not optimal, so the priority strategy for solving the problem was optimizing the planning function for handover activities. In the movement phase, a POA was prepared with indicators that were successfully achieved, namely the preparation of a revised handover SPO draft and socialization of the revised SPO draft with the nursing sector, Head Nurse, and Clinical Care Manager. In contrast, this could not be done in the refreezing phase due to time constraints, so a follow-up plan was prepared and agreed with the PIC of the activity. In conclusion, the planned change process towards optimizing effective communication during handover requires an increase in the function of nursing managers, especially in the planning function. Managers must provide policies, one of which is SOP handover, and must review and revise policies to remain new and can be applied. Keywords: Nursing Manager Function, Handover, Effective Communication, SBAR Method